Resin composition, pellet, and molded article

JP2025031640APending Publication Date: 2025-03-07MITSUBISHI ENG PLASTICS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024139268
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-23
Filing Date
2024-08-20
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0006】 本発明により、剛性、耐衝撃性、および、耐熱性に優れた樹脂組成物、ならびに、前記樹脂組成物を用いたペレット、および、成形品を提供可能になった。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031640000001
    Figure 2025031640000001
  • Figure 2025031640000002
    Figure 2025031640000002
  • Figure 2025031640000003
    Figure 2025031640000003
Patent Text Reader

Abstract

To provide a resin composition with superior rigidity, impact resistance, and heat resistance, and also to provide pellets and molded articles using the resin composition.SOLUTION: A resin composition comprises, based on 100 pts.mass of polycarbonate resin, 10-70 pts.mass of glass fibers having a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound on the surface, where the glass fibers have an average fiber length of 500 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a pellet, and a molded article. [Background technology]

[0002] Polycarbonate resins are resins that have excellent heat resistance, mechanical properties, and electrical characteristics, and are widely used, for example, as materials for automobiles, electrical and electronic equipment, housing materials, and materials for manufacturing parts in other industrial fields. In particular, polycarbonate resin compositions that have been blended with reinforcing agents such as glass fiber, carbon fiber, glass flake, talc, and mica to increase rigidity are favorably used as components for information and mobile devices such as notebook computers and smartphones, optical devices such as cameras and projectors, office automation equipment such as printers and copiers, and automobile parts. However, polycarbonate resin compositions containing such reinforcing agents have problems such as a decrease in the excellent impact resistance inherent to polycarbonate resins, and the reinforcing agent protruding onto the surface of molded articles, marring their appearance. As a method for improving the surface appearance of a polycarbonate resin composition containing a reinforcing agent, a resin composition comprising a polycarbonate resin, a fibrous filler selected from glass fiber and carbon fiber, a short fiber filler having an average fiber length of 5 to 120 μm and an average fiber diameter of 5 to 30 μm, and a phosphate ester compound has been disclosed (Patent Document 1). Also disclosed is a resin composition consisting of polycarbonate resin, glass fibers having a number average length of 10 to 50 μm, a diameter of 5 to 20 μm and a moisture content of 0.1% or less, and carbon black (Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-48912 [Patent Document 2] JP 2009-155459 A Summary of the Invention [Problem to be solved by the invention]

[0004] It was found that the resin composition described in Patent Document 1 has an excellent surface appearance, but contains a phosphoric acid ester, which impairs the heat resistance and impact resistance of the polycarbonate resin. On the other hand, it was found that the resin composition described in Patent Document 2 has an excellent surface appearance and is thought to maintain the heat resistance inherent to the polycarbonate resin, but has low impact resistance. The present invention aims to solve the above problems, and has an object to provide a resin composition excellent in rigidity, impact resistance, and heat resistance, as well as pellets and molded articles using the resin composition. [Means for solving the problem]

[0005] In light of the above-mentioned problems, the present inventors have conducted research and have found that by using glass fibers having an average fiber length of 500 μm or less and having a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound on the surface thereof, a resin composition having high rigidity, impact resistance and excellent heat resistance can be obtained, thereby completing the present invention. Specifically, the above problems were solved by the following means. <1> 100 parts by mass of polycarbonate resin, 10 to 70 parts by mass of glass fiber having a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound on its surface and an average fiber length of 500 μm or less A resin composition comprising: <2> The organosilicon compound includes a silane coupling agent and / or a silicone resin; <1> The resin composition according to claim 1. <3> The average fiber length of the glass fibers is 300 μm or less. <1> or <2> The resin composition according to claim 1. <4> Further, the composition contains 0.01 to 0.5 parts by mass of an organic sulfonic acid metal salt. <1> ~ <3> 10. The resin composition according to claim 9 . <5> Further, the composition contains an anti-dripping agent in an amount of 0.01 to 1 part by mass. <4> The resin composition according to claim 1. <6> When the resin composition is molded into a 1.5 mm thick test piece conforming to the UL-94 standard, the flame retardancy satisfies V-2 or higher. <4> or <5> The resin composition according to claim 1. <7> When the resin composition is molded into a 1.5 mm thick test piece conforming to the UL-94 standard, the flame retardancy satisfies V-0. <4> or <5> The resin composition according to claim 1. <8> The polycarbonate resin comprises recycled polycarbonate resin. <1> ~ <7> 10. The resin composition according to claim 9 . <9> When the resin composition is molded into a 4 mm thick ISO multipurpose test piece, the unnotched Charpy impact strength according to ISO179 is 70 kJ / m 2 That's all. <1> ~ <8> 10. The resin composition according to claim 9 . <10> the organosilicon compound comprises a silane coupling agent and / or a silicone resin; The average fiber length of the glass fibers is 300 μm or less, Further, the composition contains 0.01 to 0.5 parts by mass of an organic sulfonic acid metal salt, Further, the composition contains an anti-dripping agent in an amount of 0.01 to 1 part by mass, When the resin composition is molded into a 1.5 mm thick test piece conforming to the UL-94 standard, the flame retardancy satisfies V-0; the polycarbonate resin comprises recycled polycarbonate resin; When the resin composition was molded into a 4 mm thick ISO multipurpose tensile test piece, the unnotched Charpy impact strength according to ISO179 was 70 kJ / m 2 That's all. <1> ~ <9> 10. The resin composition according to claim 9 . <11> <1> ~ <10> 2. A pellet of the resin composition according to claim 1. <12> <1> ~ <10> 2. A molded article formed from the resin composition according to claim 1. <13> <11> A molded article formed from the pellets according to claim 1. Effect of the Invention

[0006] According to the present invention, it is possible to provide a resin composition having excellent rigidity, impact resistance, and heat resistance, as well as pellets and molded articles using the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.

[0008] The resin composition of the present embodiment is characterized in that it contains 100 parts by mass of polycarbonate resin, phosphorous acid and / or hypophosphorous acid, and 10 to 70 parts by mass of glass fiber having an average fiber length of 500 μm or less, the surface of which is treated with a surface treatment agent containing an organosilicon compound. With this constitution, a resin composition having high rigidity and impact resistance and excellent heat resistance can be obtained. When glass fibers having an average fiber length of 500 μm or less are used, the impact resistance tends to be poor. This is considered to be due to the glass fibers deteriorating the polycarbonate resin. In the present invention, it is presumed that by using glass fibers surface-treated with phosphorous acid and / or hypophosphorous acid and a surface treatment agent containing an organosilicon compound, the glass fibers are less likely to degrade the polycarbonate resin, even when glass fibers having an average fiber length of 500 μm or less are used, and impact resistance can be improved. Furthermore, by using glass fiber whose surface has been treated with a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound, it is possible to increase the deflection temperature under load and improve the heat resistance. Furthermore, by blending an organic sulfonic acid metal salt, which is known as a flame retardant, excellent flame retardancy can be achieved. In particular, even when an organic sulfonic acid metal salt is blended, the decrease in impact resistance can be effectively suppressed. This is presumably because the organic silicon compound and the organic sulfonic acid metal salt are less likely to adhere to the polycarbonate resin, making it easier to suppress the propagation of impact. Furthermore, even when a recycled polycarbonate resin is used as the polycarbonate resin in the resin composition of the present embodiment, the performance can be maintained without being deteriorated. The resin composition of the present embodiment will be described below.

[0009] <Polycarbonate resin> The resin composition of the present embodiment contains a polycarbonate resin. The polycarbonate resin is not particularly limited as long as it contains a -[OR-OC(=O)]- unit (wherein R is an organic group, preferably a hydrocarbon group, more preferably an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a straight-chain structure or a branched structure) containing a carbonate bond in the molecular main chain. In this embodiment, the polycarbonate resin is preferably an aromatic polycarbonate resin, and more preferably a polycarbonate resin having a bisphenol skeleton. By using such a polycarbonate resin, the obtained molded article can achieve better heat resistance and toughness. In the present embodiment, the polycarbonate resin having a bisphenol skeleton preferably has 90 mol % or more of all structural units (preferably 95 mol % or more of all structural units, more preferably all structural units excluding terminal groups) that have a bisphenol skeleton, more preferably 90 mol % or more of all structural units that have at least one skeleton of bisphenol A, bisphenol C, and bisphenol AP, and even more preferably 90 mol % or more of all structural units that have a bisphenol A skeleton.

[0010] The viscosity average molecular weight (Mv) of the polycarbonate resin is preferably 10,000 or more, more preferably 15,000 or more, and even more preferably 20,000 or more. By making it equal to or more than the lower limit, the durability of the molded article obtained tends to be further improved. The upper limit of the viscosity average molecular weight (Mv) of the polycarbonate resin is preferably 50,000 or less, more preferably 40,000 or less, even more preferably 30,000 or less, and even more preferably 25,000 or less. By making it equal to or less than the upper limit, the molding processability of the molded article tends to be further improved. The viscosity average molecular weight (Mv) was calculated by using methylene chloride as a solvent and an Ubbelohde viscometer to determine the intrinsic viscosity [η] (unit: dL / g) at 25°C, and then using the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 ×Mv 0.83 , means a value calculated from When two or more types of polycarbonate resins are used, the viscosity average molecular weight is the mixture.

[0011] The method for producing the polycarbonate resin is not particularly limited, and the polycarbonate resin produced by the conventionally known phosgene method (interfacial polymerization method) or melting method (ester exchange method) can be used, and the polycarbonate resin obtained by the interfacial polymerization method is preferable. In addition, when the melting method is used, the polycarbonate resin with the amount of OH group of the terminal group adjusted can be used.

[0012] The polycarbonate resin used in this embodiment may contain recycled products (recycled polycarbonate resin). By containing recycled products, it is expected that the environmental load can be reduced. In particular, in this embodiment, it is preferable to use recycled polycarbonate resin because the impact resistance, heat resistance, rigidity, and flame retardancy of the molded product obtained can be maintained at a high level. Examples of recycled polycarbonate resin include those obtained by material recycling in which recovered used polycarbonate resin molded products are crushed, washed, and reused, and those obtained by chemical recycling (chemical decomposition method). Chemical recycling involves chemically decomposing recovered used polycarbonate resin molded products to return them to their raw material level and resynthesize polycarbonate resin, while material recycling involves, for example, removing foreign matter from recovered used polycarbonate resin molded products, pulverizing them, washing them with an alkali, drying them, and pulverizing them into flakes or pelletizing them with an extruder. In addition, polycarbonate resin that is not a recycled polycarbonate resin may be called a virgin polycarbonate resin.

[0013] Examples of recycled polycarbonate resins include recycled polycarbonate resins derived from bottles such as water bottles, recycled polycarbonate resins derived from disks such as optical disks, recycled polycarbonate resins derived from sheets (including films), recycled polycarbonate resins derived from meter covers (e.g., power meter covers), recycled polycarbonate resins derived from headlamp lenses, and the like.

[0014] Examples of recycled polycarbonate resin include post-consumer recycled (PCR) products, which are made by collecting and recycling used products on the market, and post-industrial recycled (PIR) products, which are made by recycling materials generated in the manufacturing process of products before they are released on the market. Either type is acceptable.

[0015] In addition to the above, for details of the polycarbonate resin, the descriptions in paragraphs 0013 to 0041 of JP 2021-084942 A, the descriptions in paragraphs 0030 to 0035 of JP 2021-119211 A, and the descriptions in paragraphs 0008 to 0051 of JP 2023-083765 A can be referred to, the contents of which are incorporated herein by reference.

[0016] The content of the polycarbonate resin in the resin composition of this embodiment is preferably 58% by mass or more of the resin composition, more preferably 60% by mass or more, even more preferably 63% by mass or more, and even more preferably 65% ​​by mass or more. The upper limit of the content of the polycarbonate resin in the resin composition is preferably 90% by mass or less of the resin composition, more preferably 85% by mass or less, even more preferably 80% by mass or less, even more preferably 75% by mass or less, and may be 72% by mass or less. By making it equal to or more than the lower limit, the mechanical strength of the obtained molded product tends to be further improved. The resin composition of the present embodiment may contain only one type of polycarbonate resin, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0017] <Polycarbonate oligomer> The resin composition of the present embodiment may contain a polycarbonate oligomer. The polycarbonate oligomer is not particularly limited as long as it contains a -[OR-OC(=O)]- unit (wherein R is an organic group, preferably a hydrocarbon group, more preferably an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a linear or branched structure) containing a carbonate bond in the molecular main chain. In this embodiment, the polycarbonate oligomer is preferably an aromatic polycarbonate oligomer, and more preferably a polycarbonate oligomer having a bisphenol skeleton. By using such a polycarbonate oligomer, the obtained molded article can achieve better heat resistance and toughness. In the present embodiment, the polycarbonate resin having a bisphenol skeleton preferably has 90 mol % or more of all structural units (preferably 95 mol % or more of all structural units, more preferably all structural units excluding terminal groups) that have a bisphenol skeleton, more preferably 90 mol % or more of all structural units that have at least one skeleton of bisphenol A, bisphenol C, and bisphenol AP, and even more preferably 90 mol % or more of all structural units that have a bisphenol A skeleton.

[0018] The polycarbonate oligomer is, for example, a polycarbonate oligomer having a viscosity average molecular weight (Mv) of less than 10,000. The viscosity average molecular weight (Mv) of the polycarbonate oligomer is preferably not less than 3,000, and more preferably not more than 8,000. The viscosity average molecular weight (Mv) of the polycarbonate oligomer is measured in the same manner as the viscosity average molecular weight (Mv) of the polycarbonate resin. The incorporation of a polycarbonate oligomer tends to improve the affinity between the polycarbonate resin and the glass fiber.

[0019] When the resin composition of the present embodiment contains a polycarbonate oligomer, the content is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, even more preferably 4 parts by mass or more, and even more preferably 5 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin. By making the content equal to or more than the lower limit, the effect of improving the affinity between the polycarbonate resin and the glass fiber by the polycarbonate oligomer is further improved. In addition, the upper limit of the content of the polycarbonate oligomer is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin. The resin composition of the present embodiment may contain only one type of polycarbonate oligomer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0020] <Glass fiber having a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound on its surface and an average fiber length of 500 μm or less> The resin composition of the present embodiment contains glass fibers having a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound on the surface thereof and an average fiber length of 500 μm or less. By using such glass fibers, a resin composition capable of providing a molded product having excellent rigidity, impact resistance, and heat resistance can be obtained.

[0021] The glass fiber having a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound on its surface used in this embodiment is glass fiber treated with a surface treatment agent. The surface treatment agent contains phosphorous acid and / or hypophosphorous acid and an organosilicon compound. Usually, 80 to 100 mass % (preferably 90 to 100 mass %) of the surface treatment agent used in this embodiment is composed of phosphorous acid and / or hypophosphorous acid and an organosilicon compound. It is preferred that the phosphorous acid and / or hypophosphorous acid and the organosilicon compound react partially or entirely with each other or with the functional groups on the surface of the glass fiber.

[0022] Of the phosphorous acid and / or hypophosphorous acid, phosphorous acid is preferred. Phosphorous acid is an inorganic form of phosphorous acid (H 3 PO 3 ) is an example of hypophosphorous acid. 3 PO 2 ) is an example. It is believed that the phosphorous acid and / or hypophosphorous acid play a role in neutralizing the alkaline components of the glass with acid, thereby reducing their effect on the polycarbonate resin. The content of phosphorous acid in the glass fiber (including the amount of the surface treatment agent) is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and even more preferably 0.06 mass% or more, and is preferably 0.2 mass% or less, and more preferably 0.1 mass% or less.

[0023] The phosphorous acid and / or hypophosphorous acid treatment of glass fibers can be performed by a conventional method, such as a method of immersing and stirring a commercially available glass fiber or an untreated glass fiber in an aqueous solution of phosphorous acid and / or hypophosphorous acid having a pH of 7 or less, and volatilizing the aqueous solution by shear heat, a method of immersing glass fibers in the aqueous solution of phosphorous acid and / or hypophosphorous acid, filtering the solution, and then drying the same, or a method of spraying the aqueous solution on glass fibers and drying the same.

[0024] The organosilicon compound is a compound containing silicon atoms and carbon atoms, and preferably contains a silane coupling agent and / or a silicone resin. The organosilicon compound acts on the interface between the polycarbonate resin and the glass fiber, reducing the adhesion between them, which is believed to reduce the adverse effect of the alkaline components derived from the glass fiber on the polycarbonate resin.

[0025] Silane coupling agents include trimethylmethoxysilane, trimethylethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, trimethoxysilane, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenylmethylvinylethoxysilane, naphthyltrimethoxysilane, naphthyltriethoxysilane, 1,4-bis(methoxydimethylsilyl)benzene, and tetramethoxysilane. , tetraethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-Epoxycyclohexyl)ethylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane and its hydrochloride, N-(vinylbenzyl)-2-aminoethyl-3-aminopropylmethyldimethoxysilane and its hydrochloride, 3-isocyanate Examples of alkoxysilane compounds include alkoxysilane compounds such as ethyl propyl triethoxysilane, tris-(trimethoxysilylpropyl) isocyanurate, 3-ureidopropyl triethoxysilane, 3-chloropropyl trimethoxysilane, 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, and bis(trisethoxysilylpropyl) tetrasulfide. Of these, trimethyl methoxysilane, trimethyl ethoxysilane, dimethyl dimethoxysilane, dimethyl diethoxysilane, methyl phenyl dimethoxysilane, methyl phenyl diethoxysilane, diphenyl dimethoxysilane, diphenyl diethoxysilane, trimethoxysilane, triethoxysilane, methyl trimethoxysilane, methyl triethoxysilane, phenyl trimethoxysilane, phenyl triethoxysilane, and phenyl methyl vinyl ethoxysilane are preferred.

[0026] Silicone resins include those also called organosiloxanes and organopolysiloxanes, and refer to polymeric substances in which an organic group is added to a structure in which a silicon atom is bonded to another silicon atom via oxygen. Silicone resins are generally organic polymers with siloxane bonds as the main chain, and are generally classified into -Si(R 2)-O-. Here, R is independently a hydrogen atom, a hydrocarbon group, or a group represented by -O-hydrocarbon group, and at least one of R is a hydrocarbon group or a group represented by -O-hydrocarbon group. R is more preferably a hydrogen atom, a methyl group, an ethyl group, a phenyl group, a methoxy group, an ethoxy group, or a phenoxy group.

[0027] The weight average molecular weight (Mw) of the silicone resin used in this embodiment is not particularly limited, but is preferably 500 or more, more preferably 600 or more, even more preferably 700 or more, and particularly preferably 800 or more. It may also be preferably 2,000 or less, more preferably 1,800 or less, even more preferably 1,700 or less, even more preferably 1,500 or less, and even more preferably 1,100 or less. The weight average molecular weight of a silicone resin is measured by gel permeation chromatography (GPC) and is the average molecular weight based on mass, using styrene of known weight average molecular weight as the standard substance.

[0028] The content of the organosilicon compound in the glass fiber (including the amount of the surface treatment agent) is preferably 0.01 mass% or more, and more preferably 0.05 mass% or more, and is preferably 0.15 mass% or less, and more preferably 0.10 mass% or less. The resin composition of the present embodiment may contain only one type of organosilicon compound, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0029] The content of the surface treatment agent in the resin composition of this embodiment is preferably 0.01 mass % or more, and more preferably 0.1 mass % or more, in the glass fiber (including the amount of the surface treatment agent), and is preferably 5 mass % or less, more preferably 3 mass % or less, and even more preferably 1 mass % or less.

[0030] The resin composition of the present embodiment may contain only one type of surface treatment agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0031] Next, the glass fiber will be described. The glass fiber used in this embodiment has an average fiber length of 500 μm or less, preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and preferably 10 μm or more, more preferably 40 μm or more, and even more preferably 55 μm or more. By making it below the upper limit, the surface appearance and impact resistance of the molded product tend to be further improved. By making it above the lower limit, the elastic modulus tends to be further improved.

[0032] The glass fibers used in the present embodiment preferably have an average fiber diameter of 25 μm or less, more preferably 17 μm or less, and preferably 1 μm or more, and more preferably 5 μm or more. By making the average fiber diameter less than the upper limit and more than the lower limit, the mechanical properties tend to be further improved. In the present embodiment, when the cross section of the glass fiber is non-circular, the fiber diameter is the fiber diameter of a circle having the same area as the area of ​​the cross section. The average fiber length and average fiber diameter of the glass fibers used in this embodiment can be determined in accordance with JIS R 3420:2013 by taking 20 glass fibers from 10 g of glass fibers, measuring the fiber length and fiber diameter of each glass fiber, and taking the arithmetic mean of the measurement results. An example of the glass fiber used in this embodiment is milled fiber.

[0033] The glass fibers are selected from glass compositions such as A-glass, C-glass, E-glass, R-glass, D-glass, M-glass, and S-glass, with E-glass (alkali-free glass) being particularly preferred.

[0034] Glass fibers having a noncircular cross-sectional shape (irregular cross-sectional shape) are also preferred. The irregular cross-sectional shape has an aspect ratio, which is the long axis / short axis ratio of a cross section perpendicular to the longitudinal direction of the fiber, of, for example, 1.5 to 10, preferably 2.5 to 10, more preferably 2.5 to 8, and even more preferably 2.5 to 5.

[0035] The content of the glass fiber in the resin composition of this embodiment is 10 parts by mass or more, preferably 15 parts by mass or more, more preferably 20 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 35 parts by mass or more, even more preferably 40 parts by mass or more, and may be 45 parts by mass or more depending on the application. By making it equal to or more than the lower limit, the mechanical strength of the obtained molded article tends to be further increased. In addition, the content of the glass fiber is 70 parts by mass or less, preferably 65 parts by mass or less, more preferably 60 parts by mass or less, even more preferably 55 parts by mass or less, and even more preferably 50 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin. By making it equal to or less than the upper limit, the appearance of the molded article tends to be improved and the flowability of the resin composition tends to be further improved. The resin composition of the present embodiment may contain only one type of glass fiber, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0036] The total content of the polycarbonate resin and the glass fiber in the resin composition of this embodiment is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more in the resin composition. The total content of the polycarbonate resin and the glass fiber in the resin composition of this embodiment is preferably 99.5% by mass or less, more preferably 99% by mass or less, even more preferably 97% by mass or less, and even more preferably 96% by mass or less in the resin composition.

[0037] The resin composition of the present embodiment has a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound on its surface, and may or may not contain glass fibers other than glass fibers having an average fiber length of 500 μm or less. The resin composition of the present embodiment preferably contains substantially no other reinforcing fibers than glass fibers having a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound and an average fiber length of 500 μm or less. "Substantially free" means that the proportion of other reinforcing fibers contained in the resin composition of the present embodiment is less than 10% by mass of the content of the glass fibers, preferably less than 5% by mass, more preferably less than 3% by mass, and may be less than 1% by mass.

[0038] <Organic sulfonic acid metal salt> The resin composition of the present embodiment preferably contains an organic sulfonic acid metal salt. The organic sulfonic acid metal salt functions as a flame retardant in the polycarbonate resin and tends to improve the flame retardancy of the resulting molded article.

[0039] The organic sulfonic acid metal salt is preferably an alkali metal salt and / or an alkaline earth metal salt, and is preferably an alkali metal salt. Examples of the alkali metal include sodium, lithium, potassium, rubidium, and cesium, with sodium, lithium, and potassium being preferred, sodium and potassium being more preferred, and potassium being even more preferred. Examples of alkaline earth metal salts include beryllium, magnesium, calcium, strontium, and barium.

[0040] Of the organic sulfonic acid metal salts, metal salts of fluorine-containing aliphatic sulfonic acids and metal salts of aromatic sulfonic acids are preferred, and metal salts of fluorine-containing aliphatic sulfonic acids are more preferred. As the metal salt of fluorine-containing aliphatic sulfonic acid, the alkali metal salt of fluorine-containing aliphatic sulfonic acid having at least one C-F bond in the molecule is more preferable, and the alkali metal salt of perfluoroalkanesulfonic acid is particularly preferable. By using the metal salt of fluorine-containing aliphatic sulfonic acid, the flame retardancy and impact resistance tend to be further improved.

[0041] The molecular weight of the organic sulfonic acid metal salt is preferably 160-1,000, and more preferably 170-700.

[0042] Specific examples of the organic sulfonate metal salt that can be used in the present embodiment include alkali metal salts of fluorine-containing aliphatic sulfonic acids having at least one C-F bond in the molecule, such as potassium nonafluorobutanesulfonate (potassium perfluorobutanesulfonate), lithium nonafluorobutanesulfonate, sodium nonafluorobutanesulfonate, cesium nonafluorobutanesulfonate, lithium trifluoromethanesulfonate, sodium trifluoromethanesulfonate, potassium trifluoromethanesulfonate, potassium pentafluoroethanesulfonate, potassium heptafluoropropanesulfonate, and potassium decafluoro-4-(pentafluoroethyl)cyclohexanesulfonate;

[0043] alkaline earth metal salts of fluorine-containing aliphatic sulfonic acids having at least one C—F bond in the molecule, such as magnesium nonafluorobutanesulfonate, calcium nonafluorobutanesulfonate, barium nonafluorobutanesulfonate, magnesium trifluoromethanesulfonate, calcium trifluoromethanesulfonate, and barium trifluoromethanesulfonate;

[0044] metal salts of fluorine-containing aliphatic sulfonic acids, such as alkali metal salts of fluorine-containing aliphatic disulfonic acids having at least one C—F bond in the molecule, such as disodium difluoromethane disulfonate, dipotassium difluoromethane disulfonate, disodium tetrafluoroethane disulfonate, dipotassium tetrafluoroethane disulfonate, dipotassium hexafluoropropane disulfonate, dipotassium hexafluoroisopropane disulfonate, disodium octafluorobutane disulfonate, and dipotassium octafluorobutane disulfonate;

[0045] alkali metal salts of aromatic sulfonic acids having at least one aromatic group in the molecule, such as dipotassium diphenylsulfone-3,3'-disulfonate, potassium diphenylsulfone-3-sulfonate, potassium 3-(phenylsulfonyl)benzylsulfonate, sodium benzenesulfonate, sodium (poly)styrenesulfonate, sodium paratoluenesulfonate, sodium (branched)dodecylbenzenesulfonate, sodium trichlorobenzenesulfonate, potassium benzenesulfonate, potassium styrenesulfonate, potassium (poly)styrenesulfonate, potassium paratoluenesulfonate, potassium (branched)dodecylbenzenesulfonate, potassium trichlorobenzenesulfonate, cesium benzenesulfonate, cesium (poly)styrenesulfonate, cesium paratoluenesulfonate, cesium (branched)dodecylbenzenesulfonate, and cesium trichlorobenzenesulfonate;

[0046] Examples of the aromatic sulfonate metal salts include alkaline earth metal salts of aromatic sulfonic acids having at least one aromatic group in the molecule, such as magnesium paratoluenesulfonate, calcium paratoluenesulfonate, strontium paratoluenesulfonate, barium paratoluenesulfonate, (branched) magnesium dodecylbenzenesulfonate, and (branched) calcium dodecylbenzenesulfonate.

[0047] When the resin composition of the present embodiment contains an organic sulfonic acid metal salt, its content is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, even more preferably 0.05 parts by mass or more, even more preferably 0.08 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of polycarbonate resin. The upper limit of the content of the organic sulfonic acid metal salt is preferably 0.7 parts by mass or less, more preferably 0.5 parts by mass or less, even more preferably 0.4 parts by mass or less, even more preferably 0.35 parts by mass or less, and even more preferably 0.3 parts by mass or less, relative to 100 parts by mass of polycarbonate resin. By setting the content to be equal to or more than the lower limit and equal to or less than the upper limit, flame retardancy and impact resistance tend to be further improved. The resin composition of the present embodiment may contain only one type of organic sulfonic acid metal salt, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0048] The resin composition of the present embodiment may be configured to be substantially free of metal salts other than the metal organic sulfonate. Substantially free means that the ratio of metal salts other than the metal organic sulfonate contained in the resin composition of the present embodiment is less than 10 mass%, preferably less than 5 mass%, more preferably less than 3 mass%, and may be less than 1 mass% of the content of the metal organic sulfonate.

[0049] <Anti-drip agent> The resin composition of the present embodiment may contain an anti-dripping agent. As the drip prevention agent, a fluoropolymer is preferable, and an example of the fluoropolymer is a fluoroolefin resin. The fluoroolefin resin is usually a polymer (including a copolymer) containing a fluoroethylene structure. Specific examples include a difluoroethylene resin, a tetrafluoroethylene resin, a tetrafluoroethylene / hexafluoropropylene resin, and a tetrafluoroethylene / perfluoroalkylvinylether resin. Among them, a tetrafluoroethylene resin (PTFE) is preferable. As the fluoroethylene resin, a fluoroethylene resin having a fibril forming ability is preferable.

[0050] Examples of fluoroethylene resins having fibril-forming ability include "Teflon (registered trademark) 6J", "Teflon (registered trademark) 640J", and "Teflon (registered trademark) 6C" manufactured by Mitsui-Chemours Fluoroproducts, Inc., and "Polyflon MPAF201L", "Polyflon MPAF103", and "Polyflon MPAFA500H" manufactured by Daikin Industries, Ltd. Furthermore, examples of commercially available aqueous dispersions of fluoroethylene resins include "Teflon (registered trademark) 30J" and "Teflon (registered trademark) 31-JR" manufactured by Mitsui-DuPont Fluorochemicals, and "Fluon D-1" manufactured by Daikin Industries, Ltd.

[0051] Furthermore, fluoroethylene polymers having a multilayer structure obtained by polymerizing vinyl monomers can also be used. Examples of such fluoroethylene polymers include polystyrene-fluoroethylene polymer, polystyrene-acrylonitrile-fluoroethylene polymer, polymethyl methacrylate-fluoroethylene polymer, polybutyl methacrylate-fluoroethylene polymer, and the like. Specific examples include "Metablen A-3800" manufactured by Mitsubishi Chemical Corporation and "Brendex 449" manufactured by GE Specialty Chemicals.

[0052] When the resin composition of the present embodiment contains an anti-dripping agent, the content is preferably 0.01 parts by mass or more relative to 100 parts by mass of the polycarbonate resin, and may be 0.02 parts by mass or more or 0.03 parts by mass or more depending on the application, and is preferably 1 part by mass or less, more preferably 0.8 parts by mass or less, even more preferably 0.5 parts by mass or less, and even more preferably 0.3 parts by mass or less. By making it equal to or more than the lower limit, the effect of improving flame retardancy is more effectively exhibited, and by making it equal to or less than the upper limit, the appearance of the molded article tends to be improved. The resin composition of the present embodiment may contain only one type of anti-dripping agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0053] <Release agent> The resin composition of the present embodiment preferably contains a release agent. As the release agent, a wide variety of known release agents can be used, and examples thereof include aliphatic carboxylic acid amide compounds, aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils.

[0054] Examples of the aliphatic carboxylic acid amide compound include compounds obtained by a dehydration reaction between a higher aliphatic monocarboxylic acid and / or a polybasic acid and a diamine. As the higher aliphatic monocarboxylic acid, saturated aliphatic monocarboxylic acids and hydroxycarboxylic acids having 16 or more carbon atoms are preferred, and examples thereof include palmitic acid, stearic acid, behenic acid, montanic acid, and 12-hydroxystearic acid. Examples of polybasic acids include aliphatic dicarboxylic acids such as malonic acid, succinic acid, adipic acid, sebacic acid, pimelic acid, and azelaic acid; aromatic dicarboxylic acids such as phthalic acid and terephthalic acid; and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and cyclohexylsuccinic acid. Examples of diamines include ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, metaxylylenediamine, tolylenediamine, paraxylylenediamine, phenylenediamine, and isophoronediamine. As the carboxylic acid amide compound, a compound obtained by polycondensation of stearic acid, sebacic acid, and ethylenediamine is preferred, and a compound obtained by polycondensation of 2 moles of stearic acid, 1 mole of sebacic acid, and 2 moles of ethylenediamine is more preferred. In addition to bisamide compounds obtained by reacting diamines and aliphatic carboxylic acids, such as N,N'-methylenebisstearamide and N,N'-ethylenebisstearamide, dicarboxylic acid amide compounds, such as N,N'-dioctadecylterephthalamide, can also be suitably used.

[0055] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.

[0056] In the ester of an aliphatic carboxylic acid and an alcohol, the aliphatic carboxylic acid may be the same as the aliphatic carboxylic acid. On the other hand, the alcohol may be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic or alicyclic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred. Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol. Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, pentaerythritol tetrastearate, and esters of montanic acid and polyfunctional alcohols.

[0057] Examples of aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000 include liquid paraffin, paraffin wax, microwax, polyolefin wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. The aliphatic hydrocarbons herein also include alicyclic hydrocarbons. The number average molecular weight of the aliphatic hydrocarbons is preferably 5,000 or less.

[0058] Examples of polyolefin waxes include polyethylene wax, polypropylene wax, and polyethylene propylene wax, with polyethylene wax being preferred. The polyolefin wax may be unmodified or modified. Examples of modified polyolefin waxes include vinyl ester modified polyolefin wax, acid modified polyolefin wax, and oxidized polyolefin wax. Oxidized polyolefin wax is preferred. Oxidized polyolefin wax has excellent compatibility with polycarbonate resins and tends to effectively suppress mold deposits in the resulting resin composition.

[0059] The oxidized polyolefin wax can be obtained by oxidizing the corresponding unmodified polyolefin wax. Examples of the polyethylene wax include Licowax (registered trademark) PE520, PED521, PED522, and PED121 manufactured by Clariant; Ceridust (registered trademark) 3715, and the like. In addition to the above, commercially available polyolefin waxes can be found in paragraph 0028 of JP-A-2022-140470, the contents of which are incorporated herein by reference.

[0060] The weight average molecular weight of the polyolefin wax is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, even more preferably 2,000 or more, and even more preferably 2,500 or more. By making it equal to or greater than the lower limit, the glowing time tends to be further shortened. In addition, the weight average molecular weight of the polyolefin wax is preferably 30,000 or less, more preferably 20,000 or less, even more preferably 15,000 or less, and even more preferably 10,000 or less. By making it equal to or less than the upper limit, the flowability of the resin composition during molding tends to be further improved. The weight average molecular weight can be measured by GPC (gel permeation chromatography) using a Tosoh HLC-8320GPC EcoSEC, tetrahydrofuran as the solvent, three Shodex KF-G, KF-805L, and a KF-800D as columns, at a column temperature of 40°C and a flow rate of 1.2 mL / min, and is measured as a polystyrene equivalent value detected with a detector (UV-8320) at a detection wavelength of 254 nm. In the case where the resin composition in the present embodiment contains two or more types of polyolefin waxes, the weight average molecular weight is the weight average molecular weight of the mixture.

[0061] The dropping point of the polyolefin wax is preferably 165°C or lower, more preferably 160°C or lower, even more preferably 155°C or lower, even more preferably 150°C or lower, even more preferably 145°C or lower, even more preferably 140°C or lower, even more preferably 135°C or lower, particularly more preferably 130°C or lower, and preferably 80°C or higher, more preferably 85°C or higher, even more preferably 90°C or higher, and even more preferably 95°C or higher. The dropping point is determined by heating a polyolefin wax until it changes from a solid to a liquid state and the temperature at which the first drop of molten material falls from a standard cup having an opening of 2.8 mm.

[0062] As for the release agent, in addition to the above, the descriptions in paragraphs 0063 to 0077 of JP 2018-070722 A and the descriptions in paragraphs 0090 to 0098 of JP 2019-123809 A can be referred to, the contents of which are incorporated herein by reference.

[0063] The resin composition of the present embodiment preferably contains 0.01 parts by mass or more of the release agent relative to 100 parts by mass of the total polycarbonate resin, more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less. By making it equal to or more than the lower limit, the releasability of the obtained molded article tends to be further improved. Also, by making it equal to or less than the upper limit, the bleed-out of the obtained molded article can be effectively suppressed. The resin composition may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0064] <Coloring agent> The resin composition of the present embodiment may contain a colorant. The colorant may be a pigment or a dye, but from the viewpoint of flame retardancy, a pigment is preferred, and carbon black is preferred. For details about carbon black, please refer to paragraph 0021 of JP2011-057977A, the contents of which are incorporated herein by reference. In addition, when a colorant such as carbon black is blended into the resin composition of the present embodiment, it is preferable to form a master batch and then knead it with a polycarbonate resin, etc. For the master batch, it is preferable to use a polycarbonate resin and / or a polystyrene resin. The proportion of the colorant in the masterbatch is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, and is preferably 60% by mass or less, and more preferably 50% by mass or less.

[0065] When the resin composition of the present embodiment contains a colorant (preferably carbon black), the content thereof is preferably 0.1 part by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.4 parts by mass or more, and even more preferably 0.6 parts by mass or more, relative to 100 parts by mass of polycarbonate resin, and is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass. The resin composition of the present embodiment may contain only one type of colorant (preferably carbon black), or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0066] <Other ingredients> The resin composition of the present embodiment may contain other components other than those described above as necessary, within the scope of the present invention. Examples of other components include reactive compounds, stabilizers (thermal stabilizers, antioxidants, etc.), ultraviolet absorbers, antistatic agents, flame retardants (excluding those corresponding to organic sulfonic acid metal salts), flame retardant assistants, antifogging agents, antiblocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, water-repellent and oil-repellent agents (surfactants), compatibilizers, and chelating agents. Note that one type of other component may be contained, or two or more types may be contained in any combination and ratio. For details, please refer to paragraphs 0063 to 0067 of JP 2016-216534 A and paragraphs 0047 to 0092 of WO 2021 / 241471 A, the contents of which are incorporated herein by reference. The content of the other components in the resin composition of the present embodiment is preferably 0 to 20 mass %, more preferably 0 to 10 mass %, and further preferably 0 to 5 mass % of the resin composition. In the resin composition of the present embodiment, the total amount of the polycarbonate resin, the glass fibers, and the components blended as necessary is 100 mass %.

[0067] <Physical properties of resin composition> The resin composition of the present embodiment preferably has excellent flame retardancy. Specifically, when the resin composition of this embodiment is molded into a 1.5 mm thick test piece conforming to the UL-94 standard, the flame retardancy preferably satisfies V-2 or higher, more preferably satisfies V-1, and even more preferably satisfies V-0.

[0068] The resin composition of the present embodiment preferably has excellent impact resistance. Specifically, when the resin composition of this embodiment is molded into an ISO multipurpose test piece having a thickness of 4 mm, the unnotched Charpy impact strength according to ISO179 is 70 kJ / m 2 More preferably, it is 73 kJ / m or more. 2 More preferably, it is 75 kJ / m or more. 2More preferably, it is 80 kJ / m or more. 2 More than 100kJ / m 2 More than 110kJ / m 2 Such high impact resistance is achieved by adjusting the amount of the organic sulfonic acid metal salt.

[0069] The resin composition of the present embodiment preferably has excellent heat resistance. Specifically, when the resin composition is molded into an ISO multipurpose test piece (4 mm thick), the deflection temperature under load (DTUL) at a load of 1.8 MPa is preferably 126° C. or higher, more preferably 128° C. or higher, even more preferably 130° C. or higher, still more preferably 131° C. or higher, even more preferably 132° C. or higher, and still more preferably 133° C. or higher. Even if the upper limit of the deflection temperature under load is 150° C. or lower, the required performance is sufficiently satisfied. The flame retardancy, impact resistance and heat resistance are measured according to the description in the examples given below.

[0070] <Method of producing resin composition> There is no limitation on the method for producing the resin composition of the present embodiment, and a wide variety of known methods for producing resin compositions can be adopted. Examples of such methods include a method in which the polycarbonate resin, glass fiber, and other components to be mixed as necessary are premixed using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. It is also preferred that the glass fibers be side fed. The melt-kneading temperature is not particularly limited, but is usually in the range of 240 to 320°C.

[0071] <Molded products> The molded article of this embodiment is formed from the resin composition of this embodiment. The above-mentioned resin composition (for example, pellets) is molded into a molded article by various molding methods. The shape of the molded article is not particularly limited and can be appropriately selected depending on the use and purpose of the molded article, and examples thereof include film-like, rod-like, cylindrical, annular, circular, elliptical, polygonal, irregular, hollow, frame-like, box-like, panel-like, and button-like shapes.

[0072] The method for forming the molded article is not particularly limited, and a conventionally known molding method can be adopted, for example, injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding) molding, rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, pressure molding, etc. In particular, the resin composition of this embodiment is suitable for molded articles obtained by injection molding, injection compression molding, and extrusion molding. However, it goes without saying that the resin composition of this embodiment is not limited to molded articles obtained by these methods.

[0073] The resin composition and molded article of the present embodiment can be widely used for molded articles containing polycarbonate resin, particularly for applications requiring high rigidity and high impact resistance. Specifically, they are preferably used in electrical and electronic equipment / components, office automation equipment / components, information terminal equipment / components, machine parts, home appliances, vehicle parts (automobile interiors and exteriors), building materials, various containers, leisure goods and miscellaneous goods, lighting equipment, etc. EXAMPLES

[0074] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.

[0075] 1. Raw materials The raw materials shown in Table 1 or Table 2 below were used.

[0076] [Table 1]

[0077] [Table 2]

[0078] In Table 1 or Table 2 above, MF stands for milled fiber.

[0079] 2. Examples 1 to 15 and Comparative Examples 1 to 7 <Compound> The components shown in Table 1 or Table 2 were mixed in the ratios shown in Tables 4 to 8 (each component is in parts by mass) using a twin-screw extruder equipped with one vent. Raw materials other than glass fiber were fed into the extruder from the barrel upstream of the extruder, and glass fiber was side-fed. The materials were kneaded under conditions of a screw rotation speed of 300 rpm, a discharge rate of 200 kg / hour, and a barrel temperature of 280 to 310°C. The molten resin composition extruded in the form of strands was quenched in a water tank and pelletized using a pelletizer to obtain pellets.

[0080] <Molding of test pieces> The obtained pellets were dried at 120°C for 5 hours and then injection molded in an injection molding machine (Toyo Machinery Metals Si-80-6) at a cylinder temperature of 290°C and a mold temperature of 110°C to produce ISO multipurpose test pieces (4 mm thick).

[0081] <Charpy impact strength> Using the ISO multipurpose test pieces obtained above, the Charpy impact strength (with and without notches) was measured at 23°C in accordance with ISO179-1 and ISO179-2. The unit is kJ / m 2 As shown in.

[0082] <Flexural modulus> Using the ISO multipurpose test piece obtained above, a flat test piece of 80 mm x 10 mm x 4 mm thick was prepared, and the flexural modulus of the test piece was measured in accordance with ISO 178. The unit of elasticity was MPa.

[0083] <Deflection temperature under load> The ISO multipurpose test piece (thickness 4 mm) obtained above was used to measure the deflection temperature under load (unit: ° C.) under a load of 1.8 MPa in accordance with ISO75-1 and 2.

[0084] <Flame retardancy> The resin composition pellets obtained above were injection molded into combustion test pieces (1.5 mm thick) using an injection molding machine (SE100D manufactured by Sumitomo Heavy Industries) under conditions of a cylinder temperature of 300°C and a mold temperature of 110°C. The obtained combustion test specimens were conditioned for 48 hours in a thermostatic chamber at a temperature of 23°C and humidity of 50%, and then the flame retardancy was evaluated in accordance with the UL-94 test (combustion test of plastic materials for equipment parts). This test is a method for evaluating flame retardancy according to the following criteria based on the afterflame time and dripping property after a burner flame is brought into contact with a test specimen held vertically for 10 seconds.

[0085] [Table 3]

[0086] Afterflame time is the length of time that the combustion test specimen continues to burn with a flame after the burner is removed. Cotton ignition by dripping is a test to determine whether or not a cotton marking located approximately 300 mm below the bottom end of the combustion test specimen is ignited by dripping from the test specimen. If any of the five specimens does not meet the above criteria, it is indicated as not satisfying V-2 and is indicated as NR (not rated).

[0087] [Table 4]

[0088] [Table 5]

[0089] [Table 6]

[0090] [Table 7]

[0091] [Table 8]

[0092] As is clear from the results in Tables 4 to 8 above, the resin composition of the present embodiment was excellent in impact resistance and heat resistance. Furthermore, the flexural modulus was high and the mechanical strength was excellent. Furthermore, by incorporating an organic sulfonic acid metal salt, excellent flame retardancy was achieved.

Claims

1. Per 100 parts by mass of polycarbonate resin, 10 to 70 parts by mass of glass fibers having a surface treatment agent containing phosphorous acid and / or hypophosphorous acid and an organosilicon compound on the surface thereof and an average fiber length of 500 μm or less. A resin composition comprising:

2. The resin composition according to claim 1 , wherein the organosilicon compound comprises a silane coupling agent and / or a silicone resin.

3. The resin composition according to claim 1 or 2, wherein the glass fibers have an average fiber length of 300 μm or less.

4. The resin composition according to claim 1 or 2, further comprising 0.01 to 0.5 parts by mass of an organic sulfonic acid metal salt.

5. The resin composition according to claim 4, further comprising 0.01 to 1 part by mass of an anti-dripping agent.

6. The resin composition according to claim 4, wherein the flame retardancy of the resin composition when molded into a 1.5 mm thick test piece according to the UL-94 standard satisfies V-2 or higher.

7. The resin composition according to claim 4, wherein the flame retardancy of the resin composition when molded into a 1.5 mm thick test piece according to the UL-94 standard satisfies V-0.

8. The resin composition according to claim 1 or 2, wherein the polycarbonate resin comprises a recycled polycarbonate resin.

9. When the resin composition was molded into an ISO multipurpose test piece with a thickness of 4 mm, the unnotched Charpy impact strength according to ISO 179 was 70 kJ / m 2 The resin composition according to claim 1 or 2.

10. the organosilicon compound comprises a silane coupling agent and / or a silicone resin; The average fiber length of the glass fibers is 300 μm or less, Further, the composition contains 0.01 to 0.5 parts by mass of an organic sulfonic acid metal salt, Further, the composition contains 0.01 to 1 part by mass of an anti-dripping agent, The resin composition has a flame retardancy of V-0 when molded into a 1.5 mm thick test piece according to the UL-94 standard. the polycarbonate resin comprises recycled polycarbonate resin; When the resin composition was molded into an ISO multipurpose test piece with a thickness of 4 mm, the unnotched Charpy impact strength according to ISO 179 was 70 kJ / m 2 The resin composition according to claim 1 .

11. A pellet of the resin composition according to claim 1, 2 or 10.

12. A molded article formed from the resin composition according to claim 1, 2 or 10.

13. A molded article formed from the pellets of claim 11.

Citation Information

Patent Citations

  • Polycarbonate resin composition

    JP1997048912A

  • Glass fiber-reinforced resin composition

    JP2009155459A